2022
DOI: 10.1016/bs.apcsb.2021.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the activating mechanism of the immune system against COVID-19 by Traditional Indian Medicine: Network pharmacology approach

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) transmissions are occurring rapidly; it is raising the alarm around the globe. Though vaccines are currently available, the evolution and mutations in the SARS-CoV-2 threaten available vaccines' significance. The drugs are still undergoing clinical trials, and certain medications are approved for “emergency use” or as an “off-label” drug during the pandemic. These drugs have been effective yet accommodating side effects, which also can be lethal. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Vemurafenib and PLX-4720 are inhibitors of the B-Raf mutation V600 [ 152 , 153 ]. Vemurafenib interacts with the nucleotide-binding domain of the cell surface protein BiP, thus limiting viral replication by neutralizing viral binding [ 154 ].…”
Section: Map3k Family: a Potential Target For Antiviral Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vemurafenib and PLX-4720 are inhibitors of the B-Raf mutation V600 [ 152 , 153 ]. Vemurafenib interacts with the nucleotide-binding domain of the cell surface protein BiP, thus limiting viral replication by neutralizing viral binding [ 154 ].…”
Section: Map3k Family: a Potential Target For Antiviral Therapiesmentioning
confidence: 99%
“…In contrast, in another study, vemurafenib caused a time-dependent increase in the expression of angiotensin-converting enzyme 2 (ACE2), which may contribute to SARS-CoV-2 infection [ 155 ]. PLX-4720 interacts with receptor-interacting serine/threonine-protein kinase 1 (RIPK1) during SARS-CoV-2 infection [ 153 ]. RIPK1 is activated by nsp12 and regulates the expression of ACE2 to promote viral transmission.…”
Section: Map3k Family: a Potential Target For Antiviral Therapiesmentioning
confidence: 99%
“…In our study, we found UBE3A to interact with 14 SARS-CoV-2 and 14 MERS proteins. DCAF7 has also been reported as a drug target for COVID 19 [ 56 ]. DCAF7 is also found to interact with 14 SARS-CoV-2 and MERS proteins.…”
Section: Case Studymentioning
confidence: 99%